Brand Advocacy Driven by Customer Satisfaction: A Qualitative Perspective - Shrivastava, Kamalesh Kishore (Integrated Journal for Research in Arts and Humanities, 2023)
Brand advocacy is a powerful tool in modern marketing, driven primarily by high levels of customer satisfaction. This study examines how satisfied customers become brand advocates, influencing peer perceptions and boosting organizational success. Using qualitative methodologies, including interviews, focus groups, and case studies, the research focuses on the Indian market, where cultural factors such as collectivism and trust play critical roles. The study identifies key drivers of customer satisfaction that contribute to brand advocacy, such as service quality, emotional connection, and digital engagement. Insights from prominent Indian brands like Zomato, Tata, and Patanjali highlight the practical implications of fostering brand advocacy through customer satisfaction. Recommendations include strategies for businesses to harness this relationship to strengthen market positioning and customer loyalty.